An Experiment In Breeding Cut Roses For The Indonesian Highlands - D. P. de Vries; , Darliah; Lidwien A.M. Dubois (Zuriat, 2000)
BIOBREES is a co-operative scientific programme between Indonesia and The Netherlands, of which the rose part aims at breeding cut roses adapted to the tropical highland. Within that scope four direct plant characters of 62 cut rose genotypes in different physiological stages were studied. The genotypes originated from cross-breeding in 1995 and successive selection for cut rose properties in populations at Plant Research International, Wageningen, The Netherlands, in 1996. Plant stages stuAn died were (i) superior adult seedlings in Wageningen in 1996, (ii) clones grafted onto Natal Briar both in Wageningen and Cipanas in 1997. Clonal Plant Research International, Wageningen, Plant Research International, Wageningen, clonal plants in Cipanas had significantly shorter shoots, more thorns, smaller flowers and fewer petals than the adult seedlings in Wageningen. Clonal plants in Wageningen, however, had significantly longer shoots; more thorns, and larger flowers with more petals than the seedlings in Wageningen. Despite differences in level of expression, for each character the absence of genotype-location interaction was ascertained. The expression of characters as influenced by light (both quantitative and qualitative), temperature and cultivation is discussed in relation to selection of cut roses in the temperate zone, which are adapted to the tropical highland.